Impact of the Crystalline Li15Si4 Phase on the Self-Discharge Mechanism of Silicon Negative Electrodes in Organic Electrolytes - Bärmann, Peer; Krueger, Bastian; Casino, Simone; Winter, Martin; Placke, Tobias; Wittstock, Gunther (ACS applied materials & interfaces, 2020)
Because of their high specific capacity and rather low operating potential, silicon-based negative electrode materials for lithium-ion batteries have been the subject of extensive research over the past 2 decades. Although the understanding of the (de)lithiation behavior of silicon has significantly increased, several major challenges have not been solved yet, hindering its broad commercial application. One major issue is the low initial Coulombic efficiency and the ever-present self-discharge of silicon electrodes. Self-discharge itself affects the long-term stability of electrochemical storage systems and, additionally, must be taken into consideration for inevitable prelithiation approaches. The impact of the crystalline Li15Si4 phase is of great interest as the phase transformation between crystalline (c) and amorphous (a) phases not only increases the specific surface area but also causes huge polarization. Moreover, there is the possibility for electrochemical over-lithiation toward the Li15+a Si4 phase because of the electron-deficient Li15Si4 phase, which can be highly reactive toward the electrolyte. This poses the question about the impact of the c-Li15Si4 phase on the self-discharge behavior in comparison to its amorphous counterpart. Here, silicon thin films used as model electrodes are lithiated to cut-off potentials of 10 mV and 50 mV versus Li|Li+ (U 10mV and U 50mV) in order to systematically investigate their self-discharge mechanism via open-circuit potential (U OCP) measurements and to visualize the solid electrolyte interphase (SEI) growth by means of scanning electrochemical microscopy. We show that the c-Li15Si4 phase is formed for the U 10mV electrode, while it is not found for the U 50mV electrode. In turn, the U 50mV electrode displays an almost linear self-discharge behavior, whereas the U 10mV electrode reaches a U OCP plateau at ca. 380 mV versus Li|Li+, which is due to the phase transition from c-Li15Si4 to the a-Li x Si phase. At this plateau potential, the phase transformation at the Si|electrolyte interface results in an electronically more insulating and more uniform SEI (U 10mV electrode), while the U 50mV electrode displays a less uniform SEI layer. In summary, the self-discharge mechanism of silicon electrodes and, hence, the irreversible decomposition of the electrolyte and the corresponding SEI formation process heavily depend on the structural nature of the underlying lithium–silicon phase.